Sensory interaction system - CHEN JIE; RUAN LUSHA; MA JIANA; ZHANG YEMENG; WU QINGHANG (2024)
The invention relates to the technical field of communication, and provides a communication sensing interaction system, which comprises a service module used for carrying out communication sensing service processing; the communication module is used for realizing communication connection between the terminals; the general inductance data processing module is used for processing the general inductance data channels and the general inductance data transmitted by the AIoTel SDK modules to obtain general inductance interaction data, and sending the general inductance interaction data to the corresponding AIoTel SDK modules based on the general inductance data channels; and the AIoTel SDK module is configured on the terminal and is used for acquiring the general inductance data in the communication connection process, sending the general inductance data to the general inductance data processing module based on the general inductance data channel and realizing general inductance interaction on the terminal based on